Active Evaluation: Efficient NLG Evaluation with Few Pairwise Comparisons - Mohankumar, Akash Kumar; Khapra, Mitesh M. (ACL 2022, 2022)
Recent studies have shown the advantages of evaluating NLG systems using pairwise comparisons as opposed to direct assessment. Given systems, a naive approach for identifying the top-ranked system would be to uniformly obtain pairwise comparisons from all () pairs of systems. However, this can be very expensive as the number of human annotations required would grow quadratically with . In this work, we introduce Active Evaluation, a framework to efficiently identify the top-ranked system by actively choosing system pairs for comparison using dueling bandit algorithms. We perform extensive experiments with 13 dueling bandits algorithms on 13 NLG evaluation datasets spanning 5 tasks and show that the number of human annotations can be reduced by 80%. To further reduce the number of human annotations, we propose model-based dueling bandit algorithms which combine automatic evaluation metrics with human evaluations. Specifically, we eliminate sub-optimal systems even before the human annotation process and perform human evaluations only on test examples where the automatic metric is highly uncertain. This reduces the number of human annotations required further by 89%. In effect, we show that identifying the top-ranked system requires only a few hundred human annotations, which grow linearly with . Lastly, we provide practical recommendations and best practices to identify the top-ranked system efficiently. Our code has been made publicly available on GitHub.